CLINICAL AND PSYCHOPATHOLOGYCAL DISORDERS AT POISONING BY CARBON MONOXIDE - Sharko, O.N. (World of Medicine and Biology, 2012)
Conducted the analysis of clinical psychopathology violations is conducted for victims as a result of poisoning by carbon monoxide (CM). As a result of the conducted research the abnormal clinical psychopathology features of psychonosemas are certain depending on a measure and stage of poisoning by CM. Basic conformities to law of psychopathogenesis of these violations, main from which are influence of anoxemia which arises up as a result of connection of carbon monoxide with haemoglobin, metabolic violations in the tissues of brain as a result of influence of CM, are set, cytotoxical action of CM and remote destructions of tissues of brain.